Asymmetrical Periflexural Exanthem Associated with SARS-CoV-2 Infection in a Paediatric Patient - Adriana Valencia-Herrera; Luciana Ganoza-Granados; Karen Camargo-Sánchez; Yazmín A. Chirino-Barceló; Mirna Toledo-Bahena (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)